Does deep bradycardia increase the risk of arrhythmias and syncope in endurance athletes? - Matelot, D.; Schnell, F.; Khodor, N.; Endjah, N.; Kervio, G.; Carrault, G.; Thillaye du Boullay, N.; Carre, F. (International Journal of Sports Medicine, 2016)
The aim of this study was to evaluate whether endurance athletes who exhibit deep bradycardia are more prone to arrhythmias and reflex syncope than their non-bradycardic peers. 46 healthy men (ages 19-35) were divided into 3 groups based on whether they were sedentary (SED,<2 h/week) or endurance trained (ET,>6 h/week), and non-bradycardic (NB, resting heart rate (HR)=60?bpm) or bradycardic (B, resting HR<50 bpm). Resting HR was lower in ETB vs. ETNB and SED (43.8±3.1, 61.3±3.3, 66.1±5.9 bpm, respectively; p<0.001). Thus, 16 SED, 13 ETNB and 17 ETB underwent resting echocardiography, maximal exercise test, tilt test (TT) and 24 h-Holter ECG. Subjects were followed-up during 4.7±1.1 years for training, syncope and cardiac events. Our results showed that incidence of arrhythmias and hypotensive susceptibility did not differ between groups. During follow-up, no episode of syncope or near-syncope was reported. However, cardio-inhibitory syncope occurrence tended to be higher in ETB. Left ventricular end-diastolic diameter index was increased in ETB vs. ETNB and was correlated with resting HR (r=- 0.64; p<0.001). As a result, athletes with deep bradycardia do not present more arrhythmias and more hypotensive susceptibility than their non-bradycardic peers. Cardiac enlargement and autonomic alteration both seem to be involved in an athlete`s bradycardia.